Updated meta-analysis of fractional flow reserve versus coronary angiography for guiding percutaneous coronary intervention - Fahui Yin; Yong Zhang; Xueqian Zhang; Yangang Chen; Xuelian Cui (PLoS ONE, 2025)
Background: Fractional Flow Reserve (FFR) has been widely utilized in clinical practice for decades,however, the comparative clinical outcomes of FFR-guided versus coronary angiography (CAG)-guided percutaneous coronary intervention (PCI) still warrant further evaluation. Methods and materials: Randomized controlled trials (RCTs) comparing FFR-guided and CAG-guided PCI were systematically searched in PubMed, Embase and the Cochrane library databases from their respective inception to December 31, 2023. Primary endpoints included the incidence of major adverse cardiovascular events (MACE), all cause mortality, myocardial infarction (MI) and target vessel revascularization(TVR). Stratified analyses were performed to evaluate the effects of FFR-guided versus CAG-guided PCI across different follow-up periods (short-term and long-term) and patient cohorts (acute coronary syndrome (ACS) and non-ACS patients). Results: This meta-analysis included eight RCTs involving 4,433 patients, with four studies reporting 1-year outcomes and four reporting outcomes beyond one year. Among these, 5 studies focused on non-ACS patients, and three included ACS patients, with a significant male predominance (3,437 vs. 996 females). By follow-up duration, FFR-guided PCI demonstrated significant long-term reductions in MACE (OR: 0.76, 95% CI: 0.60-0.96, P = 0.022) and MI (OR: 0.65, 95% CI: 0.45-0.93, P = 0.018), but no significant short-term benefits were observed for MACE (OR: 0.85, 95% CI: 0.67-1.08, P = 0.194), MI (OR: 0.85, 95% CI: 0.63-1.16, P = 0.307), or all-cause mortality (short-term: OR: 0.77, 95% CI: 0.47-1.26, P = 0.296; long-term: OR: 0.74, 95% CI: 0.50-1.09, P = 0.123). By patient type, FFR-guided PCI significantly reduced MACE (OR: 0.82, 95% CI: 0.68-0.99, P = 0.038), MI (OR: 0.76, 95% CI: 0.58-0.99, P = 0.039), and TVR (OR: 0.78, 95% CI: 0.61-0.99, P = 0.036) in non-ACS patients, but no significant differences were observed in ACS patients for MACE (OR: 0.76, 95% CI: 0.53-1.08, P = 0.127), all-cause mortality (OR: 0.60, 95% CI: 0.35-1.02, P = 0.060), MI (OR: 0.77, 95% CI: 0.47-1.25, P = 0.294), or TVR (OR: 0.98, 95% CI: 0.48-2.02, P = 0.315). Sensitivity analysis confirmed the robustness of these findings. Conclusions: FFR-guided PCI is superior to CAG-guided PCI in reducing MACE and MI in long-term and non-ACS patients but shows no advantage in short-term or ACS populations. FFR should be avoided in patients presenting with ACS in routine clinical practice.